The Long Odyssey of Chauncey Sheldon, a Survivor of the 1838 Patriot War: His Story - Carter, John (Ontario History)

(untitled) (The Ontario Historical Society, 2023)
Between December 1837 and December 1838, there were at least 14 recorded armed and unsanctioned incursions from United States into Upper Canada undertaken by what was referred to as the “Patriot Army.” Its intention was to overthrow what was seen by some as “oppression” and “British tyranny.” While none of these raids were successful, over 1,000 men involved with these raids were arrested, many of whome were charged with piratical invasion/high treason. One of those men was Chauncey Sheldon. This is his story.